Developing Joint Development Zone in Disputed Maritime Boundaries - Aziz, Muhammad Faiz (UI Scholars Hub, 2018)
As an archipelagic country, Indonesia has more maritime boundaries than land boundaries. There are 10 countries directly adjacent to Indonesia. Of those countries, Indonesia has just reached a few conclusive bilateral arrangements on maritime boundaries. Many unresolved and potential disputes are there that may arise in the future. Two ways have been used to negotiate Indonesia’s maritime boundaries: (1) bilateral talks that result in bilateral agreements and (2) dispute settlement through an international tribunal. However, for more than 50 years, these two methods have not optimally provided the expected result. In fact, the islands of Sipadan-Ligitan have been gone to Malaysia after Indonesia lost in the International Court of Justice. Creating a joint development zone will be good alternative mechanism proposed for the Indonesian government to resolve its dispute especially in an area that has natural resources. Indonesia once created a bilateral treaty on joint development zone with Australia on the Timor Gap and in fact, the treaty was considered a good example. Malaysia-Thailand and Malaysia-Vietnam are among the real examples in the implementation of joint development zones that still ongoing until today. Looking at the advantages and disadvantages of this zone, this alternative dispute resolution may be considered to provide the best solution for disputed countries. Moreover, this is supported by Article 74 paragraph 3 and Article 83 paragraph 3 of the United Nations Convention on the Law of the Sea (UNCLOS) 1982. The creation of relevant and effective agreement, regulatory and institutional frameworks becomes the Indonesian government’s homework to optimize this mechanism.